Biomedical engineering aspects of nanocellulose: a review. (3rd September 2022) - Rai, Rohit; Dhar, Prodyut
Abstract: Cellulose is one of the most abundant renewable biopolymer in nature and is present as major constituent in both plant cell walls as well as synthesized by some microorganisms as extracellular products. In both the systems, cellulose self-assembles into a hierarchical ordered architecture to form micro to nano-fibrillated structures, on basis of which it is classified into various forms. Nanocellulose (NCs) exist as rod-shaped highly crystalline cellulose nanocrystals to high aspect ratio cellulose nanofibers, micro-fibrillated cellulose and bacterial cellulose (BC), depending upon the origin, structural and morphological properties. Moreover, NCs have been processed into diversified products ranging from composite films, coatings, hydrogels, aerogels, xerogels, organogels, rheological modifiers, optically active birefringent colored films using traditional-to-advanced manufacturing techniques. With such versatility in structure-property, NCs have profound application in areas of healthcare, packaging, cosmetics, energy, food, electronics, bioremediation, and biomedicine with promising commercial potential. Herein this review, we highlight the recent advancements in synthesis, fabrication, processing of NCs, with strategic chemical modification routes to tailor its properties for targeted biomedical applications. We also study the basic mechanism and models for biosynthesis of cellulose in both plant and microbial systems and understand the structural insights of NC polymorphism. The kinetics study for both enzymatic/chemical modifications of NCs and microbial growth behavior of BC under various reactor configurations are studied. The challenges associated with the commercial aspects as well as industrial scale production of pristine and functionalized NCs to meet the growing demands of market are discussed and prospective strategies to mitigate them are described. Finally, post chemical modification evaluation of biological and inherent properties of NC are important to determine their efficacy for development of various products and technologies directed for biomedical applications.